2021
DOI: 10.1111/mcn.13228
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: A family systems approach to promote maternal, child and adolescent nutrition

Abstract: In all cultures, women and children are embedded in family systems that determine roles, relationships, patterns of communication and authority between family members. Especially in non‐western societies, maternal and child nutrition practices are determined not only by the biological parents but also by other influential family members. Most maternal and child nutrition research and interventions do not consider the constellation of family roles and influence on women and children and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Indeed, several studies have supported expanding the focus of nutritional programming beyond the mother–child dyad to include other influential household members. Grandmothers in non-Western societies, including Kenya, play a significant role in both advising young mothers and caring for women and children in the household, particularly related to nutrition and health ( 10 , 13 , 15 , 44 ). One study in Vietnam showed potential for improving rates of EBF by directly targeting fathers with mass media communication, group counseling, individual counseling, and social public events ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have supported expanding the focus of nutritional programming beyond the mother–child dyad to include other influential household members. Grandmothers in non-Western societies, including Kenya, play a significant role in both advising young mothers and caring for women and children in the household, particularly related to nutrition and health ( 10 , 13 , 15 , 44 ). One study in Vietnam showed potential for improving rates of EBF by directly targeting fathers with mass media communication, group counseling, individual counseling, and social public events ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that many of these interventions for fathers additionally incorporated distinct content to strengthen aspects of couples' relationships and father engagement more broadly in childcare and household responsibilities spanning beyond nutrition and health. This combination of content addressing both fathers' dyadic nurturing care with their children and relationships with their partners reflects a family systems perspective on father involvement, which has shown increasing empirical support and cross-cultural relevance in LMICs 5,86. While nutrition and health were the most common program areas, our review also uncovered a recent expansion of more multicomponent fatherhood interventions, particularly with attention to responsive parenting, violence prevention, mental health, and gender norms.For example, two couples interventions in Rwanda 63 and Burkina Faso 61 and one intervention specifically for fathers in Uganda 54 jointly promoted messages to increase paternal nurturing care behaviors for their children and to enhance fathers' relationships with their TA B L E 4 Reported enablers of program implementation with fathers Theme Illustrative quote from article…”
mentioning
confidence: 78%
“…The importance of home visits has been reinforced in recent literature (Rhodes et al, 2021; United Nations Children's Fund [UNICEF], & WHO, 2021). The strength of evidence for the importance of community engagement, including via CHW, and family involvement from fathers and grandmothers, continues to grow (Aubel et al, 2021). At the individual level, digital health interventions offer promising new opportunities for improving breastfeeding outcomes, but better‐quality research design is necessary to ascertain the most effective types of interventions.…”
Section: Discussionmentioning
confidence: 99%